Poverty and the Rate of Time Preference: Evidence from Panel Data - Lawrance, Emily C. (Journal of Political Economy, 1991)
This paper uses the Panel Study of Income Dynamics to study the intertemporal preferences of rich and poor households in the United States. Subjective rates of time preferences, identified from estimation of consumption Euler equations, are three to five percentage points higher for households with low permanent incomes than for those with high permanent incomes. Controlling for race and education widens this difference. With age and family composition held constant, time preference rates vary from 12 percent for white, college-educated families in the top 5 percent of the labor income distribution to 19 percent for nonwhite families without a college education whose labor incomes are in the bottom fifth percentile. Copyright 1991 by University of Chicago Press.